PERLINDUNGAN HUKUM PADA PROSES PENYIDIKAN TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PERSETUBUHAN DENGAN KEKERASAN - SUKAMTO, EDI (Dinamika Hukum, 2017)
The purpose of this study is to analyze the legal protection of child victims of intercourse in the jurisdiction of Sragen Police and its obstacles. This research is included in the type of sociological juridical research. The type of data needed is secondary and primary data. Secondary data obtained through literature study, while the primary data obtained by interview. Data analysis is done qualitatively. The results of the study showed that the protection of victims of sexual intercourse was conducted based on the law as a legal product that must be in favor of the victim. Obstacles in the protection of victims of sexual intercourse are psychic. In addition, victims are often not open to tell the story. Keywords: Legal Protection, Child, Investigation, Criminal Act Intercourse.